Standardized protocol of blood pressure measurement and quality control program for the Korea National Health and Nutrition Examination Survey - Hack-Lyoung Kim; Sang Min Park; In Jeong Cho; Yu-Mi Kim; Dae-Hee Kim; Sung Hye Kim; Kwang-Il Kim; Ki-Chul Sung; Sang-Hyun Ihm; Jinho Shin; Yoonjung Kim; Kyungwon Oh; et al. (BMC, 2023)
Abstract Accurate blood pressure (BP) measurement is crucial for hypertension detection and management. The Korea National Health and Nutrition Examination Survey (KNHANES) assesses the health of Koreans using representative cross-sectional data. BP measurements were historically done with mercury sphygmomanometers for participants aged ≥10 years. However, KNHANES transitioned to Greenlight 300TM (mercury-free auscultatory device) in 2020 for participants aged ≥6 years and used dual devices (Microlife WatchBP Office AFIB and Greenlight) in 2021-2022. To ensure consistency, KNHANES will adopt Microlife as the unified BP device with Greenlight for device validation from 2023. Under the new protocol, participants aged ≥6 years will have their BP measured three times at 30-second intervals after a 5-minute rest under ambient temperature (20-25℃) and noise ≤65 dB. The average of the 2nd and 3rd readings will be used as the representative BP value. The quality control (QC) program involves four trained examiners passing the "quality control and assurance of BP measurement program" three times annually, and undergoing "video monitoring of weekly calibration process" once a year. Additionally, the QC team will conduct "on-site evaluations of BP measurement" at mobile examination centers three times a year. A Five-Step QC process for BP devices was also developed. This document outlines the standardized BP measurement protocol and rigorous QC program in KNHANES, aiming to ensure accurate and reliable BP data for epidemiological research and public health policymaking in South Korea. Graphical Abstract